Analyses of thrombi in acute ischemic stroke: A consensus statement on current knowledge and future directions. Issue 6 (August 2017) - De Meyer, Simon F; Andersson, Tommy; Baxter, Blaise; Bendszus, Martin; Brouwer, Patrick; Brinjikji, Waleed; Campbell, Bruce CV; Costalat, Vincent; Dávalos, Antoni; Demchuk, Andrew; Dippel, Diederik; Fiehler, Jens; et al.
Limited data exist on clot composition and detailed characteristics of arterial thrombi associated with large vessel occlusion in acute ischemic stroke. Advances in endovascular thrombectomy and related imaging modalities have created a unique opportunity to analyze thrombi removed from cerebral arteries. Insights into thrombus composition, etiology, physical properties and neurovascular interactions may lead to future advancements in acute ischemic stroke treatment and improved clinical outcomes. Advances in imaging techniques may enhance clot characterization and inform therapeutic decision-making prior to treatment and reveal stroke etiology to guide secondary prevention. Current imaging techniques can provide some information about thrombi, but there remains much to evaluate about relationships that may exist among thrombus composition, occlusion characteristics and treatment outcomes. Improved pathophysiological characterization of clot types, their properties and how these properties change over time, together with clinical correlates from ongoing studies, may facilitate revascularization with thrombolysis and thrombectomy. Interdisciplinary approaches covering clinical, engineering and scientific aspects of thrombus research will be key to advancing the understanding of thrombi and improving acute ischemic stroke therapy. This consensus statement integrates recent research on clots and thrombi retrieved from cerebral arteries and provides a rationale for further analyses, including current opportunities and limitations.